Understanding Curriculum Transformations Towards the Creation of Sustainable Learning Environments: A Posthumanist Reflection - Makeresemese, Mahlomaholo Rosy; Mahlomaholo, Mahlomaholo Geoffrey (Research in Social Sciences and Technology, 2023)
This paper uses posthumanism as the theoretical framing to understand the curriculum transformations towards creating sustainable learning environments at some higher education institutions (HEIs) and the early childhood care and education (ECCE) centres in South Africa. The choice of these two bands in education is necessitated by the fact that curriculum singularities and/or insularities have become obsolete in the context of the Covid-19 pandemic and its aftermath, the calls for decolonization of the curriculum and the challenges of the Fourth Industrial Revolution (4IR). For example, COVID-19 has demonstrated that the curriculum is best delivered when various actors, different modes of interaction and distributed sites are used to ensure no learner is left behind, irrespective of their station in life. Emphasizing the same notions of multi-layered and multi-perspectival approaches, the calls for decolonization affirm the importance of all canons of knowledge, beyond just the euro-centric ones, as the basis for a transformed curriculum. Furthermore, the 4IR privileges the skills of collaboration and compassion for others as critical in this era. What the article brings forth as the central idea is the primacy of relationalities in the construction of curriculum, hence the identities of learners, students, academics, caregivers, institutions of higher learning and care centres. The above are beyond the deleterious influences of anthropocentrism, hence the Anthropocene, and the individuality of humanism and enlightenment. Creating sustainable learning environments is the primary goal of all curricula across the globe. The challenge thus far has been the curriculum approaches that isolate individuals and/or processes from the stakeholders and role players. Curricula emphasized the lone genius’s power and prowess, relying almost solely on their innate abilities as advised by genetic epistemology; this was despite the incessant caution by socio-culturalism and eco-systemic couplings. The latter advocates for the focus on relationalities as a basis for curriculum quality assurance and its transformations. To evidence the above, this article traces how the scholars and practitioners of the curriculum at HEIs and ECCE in South Africa have shifted focus from an emphasis on isolationism to collaboration and the privileging of relationalities. The article highlights the nature and the specificity of those changes and how they relate to new curriculum experiences.